Anti-amoebic effects of selected herbal extracts against Acanthamoeba species isolated from different borehole water samples from Budiriro District in Harare, Zimbabwe - Kudzai Fambisai; Petros Muchesa; Farisai Chidzwondo; Rumbidzai Mangoyi (Infectious Diseases and Herbal Medicine)
Acanthamoeba species are the major cause of Acanthamoeba Keratitis (AK) of eyes, Acanthamoeba meningoencephalitis of the central nervous system, and fatal Granulomatous Amoebic Encephalitis (GAE) of the brain in humans. These diseases are difficult to treat due to their resistance to extreme temperatures, pH, alcohol, and pressure. This research aimed to determine the anti-amoebic effects of some selected plant extracts against Acanthamoeba species isolated from borehole water samples from Budiriro District, Harare, Zimbabwe. Acanthamoeba castellannii species were isolated and confirmed present in Budiriro borehole water samples using non-nutrient agar, microscope, real-time Polymerase Chain Reaction (PCR), and gel electrophoresis. The selected plant samples, Murumanyama (Xeroderris stuhlmannii) bark extract, Munhundurwa (Solanum incanum) fruit extract and Mufandichimuka (Myrothamnus flabellifolius) stem and leaf extracts were then investigated for their anti-amoebic effects against the isolated Acanthamoeba castellannii, using agar well diffusion method. Chlorhexidine gluconate antibiotic was used as a control. The results show that Acanthamoeba castellannii is the most common Acanthamoeba species in borehole water in Budiriro District in Harare and all the tested plant samples had no anti-amoebic effects against this isolated Acanthamoeba castellannii.